2015
DOI: 10.18632/oncotarget.3345
|View full text |Cite
|
Sign up to set email alerts
|

High neuropeptide Y release associates with Ewing sarcoma bone dissemination -in vivomodel of site-specific metastases

Abstract: Ewing sarcoma (ES) develops in bones or soft tissues of children and adolescents. The presence of bone metastases is one of the most adverse prognostic factors, yet the mechanisms governing their formation remain unclear. As a transcriptional target of EWS-FLI1, the fusion protein driving ES transformation, neuropeptide Y (NPY) is highly expressed and released from ES tumors. Hypoxia up-regulates NPY and activates its pro-metastatic functions. To test the impact of NPY on ES metastatic pattern, ES cell lines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 51 publications
4
34
0
Order By: Relevance
“…In support of this hypothesis, we reported that the degree of bone destruction in Ewing sarcoma primary tumors derived from our in vivo xenograft model correlated with the level of NPY release from these tumors and was significantly reduced by NPY shRNA (Hong et al, 2015). Moreover, in these primary osseous tumors, the expression of NPY exhibited a characteristic gradient, with an increased intensity of NPY immunostaining in tumor cells directly surrounding bone invasion areas, as compared to cells distant from bone.…”
Section: Bone Invasionsupporting
confidence: 73%
See 2 more Smart Citations
“…In support of this hypothesis, we reported that the degree of bone destruction in Ewing sarcoma primary tumors derived from our in vivo xenograft model correlated with the level of NPY release from these tumors and was significantly reduced by NPY shRNA (Hong et al, 2015). Moreover, in these primary osseous tumors, the expression of NPY exhibited a characteristic gradient, with an increased intensity of NPY immunostaining in tumor cells directly surrounding bone invasion areas, as compared to cells distant from bone.…”
Section: Bone Invasionsupporting
confidence: 73%
“…Since hypoxia facilitates the development of distant metastases, and cancer stem cells are believed to be responsible for their initiation, our data strongly implicate the NPY axis as a mediator of this effect (Das et al, 2008; Mujcic et al, 2014; Toffoli and Michiels, 2008; Zhou and Zhang, 2008). In line with this notion, in the in vivo model of Ewing sarcoma, NPY and Y5R were highly up-regulated in distant metastases, as compared to the corresponding primary tumors (Hong et al, 2015). Expression of Y2R, in turn, was elevated in tissues derived from local relapses, suggesting its role in tumor cell invasiveness.…”
Section: Tumor Invasiveness and Metastasessupporting
confidence: 54%
See 1 more Smart Citation
“…Thus, we demonstrate that in vivo miR-130b is able to significantly alter ES dissemination, with organ tropism most likely dependent on inherent properties of the cell line. TC71 has been shown to have the ability to metastasize to the lungs in prior studies, while our experience with MHH-ES-1 cells have demonstrated propensity for metastasis to the liver, which might be attributed to their derivation from ascites fluid of the abdomen 30,31 . Overall our in vitro and in vivo studies provide convincing evidence that miR-130b contributes to metastatic properties and phenotype seen in ES tumors.…”
Section: Resultsmentioning
confidence: 73%
“…Earliest xenotransplantation models were injected either subcutaneously or intravenously in nude or NOD/scid mice [93][94][95] . Later murine models sought to more closely resemble the native tumour environment by performing orthotopic xenografts in rib bones [96] , femur [97] , pretibial space [98] , and gastrocnemius muscles [99] . Not only new compounds are tested but also novel drug delivery methods, such as silk gel to effectuate a sustained release of chemotherapeutics locally [100] .…”
Section: In Vivo Modelsmentioning
confidence: 99%